Species-Associated Differences in the Below-Ground Microbiomes of Wild and Domesticated Setaria - Chaluvadi, Srinivasa; Bennetzen, Jeffrey L. (Frontiers in Plant Science, 2018)
The rhizosphere microbiome is known to play a crucial role in promoting plant growth, partly by countering soil-borne phytoparasites and by improving nutrient uptake. The abundance and composition of the rhizosphere and root-associated microbiota are influenced by several factors, including plant species and genotype. We hypothesize that crop domestication might influence the composition and diversity of plant-associated microbiomes. We tested the contribution of domestication to the bacterial and archaeal root and soil composition associated with six genotypes of domesticated Setaria italica and four genotypes of its wild ancestor, S. viridis. The bacterial microbiome in the rhizoplane and root endophyte compartments, and the archaea in the endophyte compartment, showed major composition differences. For instance, members of the Betaproteobacteria and Firmicutes were overrepresented in S. italica root samples compared to S. viridis. Metagenomic analysis of samples that contained both root surface-bound (rhizoplane) and inside-root (endophytic) bacteria defined two unique microbial communities only associated with S. italica roots and one only associated with S. viridis roots. Root endophytic bacteria were found in six discernible communities, of which four were primarily on S. italica and two primarily on S. viridis. Among archaea, Methanobacteria, and Methanomicrobia exhibited species-associated differences in the rhizosphere and root compartments, but most detected archaea were not classified more specifically than at the level of phylum. These results indicate a host genetic contribution to the microbial composition in Setaria, and suggest that domestication has selected for specific associations in the root and in the rhizosphere.